Description of the first cave dwelling species of the spider genus Trilacuna Tong & Li from Iran (Araneae: Oonopidae) - Hosseini, Mohammad-Javad Malek; Grismado, Cristian J.; Sadeghi, Saber; Bakhshi, Yaser (Zootaxa, 2015)
A new species of the hard-bodied oonopid genus Trilacuna Tong & Li is described from a cave in Kohgiluyeh and Boyer-Ahmad Province, southwestern Iran. Trilacuna qarzi sp. nov. is the first troglobiont species known of the genus, and is also the fifth oonopid species to be reported from Iran. Relationships of this new species are briefly discussed in the context of the limits of the genera belonging to the Dysderoides complex.